진행하는 원추각막 환자에서 전통적 각막 교차결합술 시행 후 10년간의 임상결과 - 이준우(Junwoo Lee); 손보권(Bo Kwon Son); 김태기(Tae Gi Kim); 진경현(Kyung Hyun Jin) (Daihan angwa haghoi jabji, 2022)
목적: 진행성 원추각막 환자에서 전통적 각막 교차결합술 시행 후 10년간의 결과를 통해 장기적인 치료 효과를 알아보고자 하였다. 대상과 방법: 양안 원추각막으로 진단받은 9명 18안을 대상으로, 기준에 따라 진행성으로 판단되어 전통적 각막 교차결합술을 시행한9안과, 초기에 진행성으로 판단되지 않아 경과 관찰을 시행한 반대 안의 결과를 후향적으로 분석하였다. 모든 안에서 시술 전, 시술후 1, 3, 6개월 및 1년부터 10년까지 매년 최대교정시력 측정 및 각막 지형도 검사를 시행하였다. 결과: 전통적 각막 교차결합술을 시행받은 치료 안의 최대교정시력은 시술 전 0.63 ± 0.18 logMAR에서 10년 후 0.46 ± 0.25 logMAR 로 유의한 호전을 보였다(p=0.027). 최대각막곡률치 및 평균각막곡률치는 각각 65.90 ± 9.43 diopters (D), 52.82 ± 5.16 D에서62.83 ± 8.16 D, 51.52 ± 5.18 D로 감소하였고(각각 p=0.021, p=0.028) 각막난시는 6.97 ± 2.21 D에서 5.53 ± 1.64 D로 감소하였다(p=0.008). 반대 안은 경과 관찰 4년 후부터 평균각막곡률치가 유의하게 증가하였으나 다른 수치는 유의하게 변화하지 않았다. 각막교차결합술 후 3안에서 각막혼탁이 10년 뒤까지 지속되었지만, 각막혼탁을 보이지 않은 군과 최대교정시력 변화량의 유의한 차이는보이지 않았다(p=0.714). 결론: 진행성 원추각막 환자에서 전통적 각막 교차결합술은 시술 후 장기간 동안 진행을 억제하는 안전하고 효과적인 시술임을 확인할 수 있다. Purpose: To evaluate the long-term effects of conventional corneal cross-linking in patients with progressive keratoconus. Methods: A total of 18 eyes of 9 patients diagnosed with keratoconus were analyzed retrospectively. One eye was diagnosed with progressive keratoconus and conventional corneal crosslinking was performed. The other eye was classified as non-progressive and remained untreated. All patients were assessed with best corrected visual acuity (BCVA), maximum keratometry (Kmax), mean keratometry (Kmean), corneal astigmatism, and corneal thickness. Clinical data were collected before the procedure and at 1, 3, 6 months and 1 to 10 years after the procedure. Results: The BCVA significantly improved from 0.63 ± 0.18 logarithm of the minimum angle of resolution (logMAR) to 0.46 ± 0.25 logMAR at 10 years after conventional corneal crosslinking (p = 0.027). The Kmax and Kmean decreased from 65.90 ± 9.43 D and 52.82 ± 5.16 D to 62.83 ± 8.16 D and 51.52 ± 5.18 D, respectively (p = 0.021, p = 0.028, respectively). Corneal astigmatism decreased from 6.97 ± 2.21 D to 5.53 ± 1.64 D (p = 0.008). The thinnest corneal thickness decreased from 435.11 ± 53.37 μm to 369.22 ± 64.00 μm 1 month after the procedure (p = 0.008), and gradually improved over time. At 10 years, the thinnest corneal thickness increased to 410.11 ± 61.32 μm (p = 0.097). In the untreated eyes, the mean keratometry significantly increased after 4 years of follow-up, but other factors did not change significantly. Although corneal opacity persisted for up to 10 years in 3 eyes of the treatment group, there was no significant difference of BCVA compared to the treated eyes without corneal opacity (p = 0.714). Conclusions: In patients with progressive keratoconus, conventional corneal crosslinking is a safe and effective procedure that suppresses long-term progression. KCI Citation Count: 0